2000
DOI: 10.1016/s0925-4439(99)00097-6
|View full text |Cite
|
Sign up to set email alerts
|

Inositol phosphoryl transferases from human pathogenic fungi

Abstract: The IPC1 gene from Saccharomyces cerevisiae, which encodes inositolphosphorylceramide (IPC) synthase, was first identified as a novel and essential gene encoding resistance to the natural product antifungal aureobasidin A (AUR1). The formation of IPC in fungi is essential for viability, suggesting inhibitors of IPC1p function would make ideal antifungal drug candidates. Homologs of the AUR1/IPC1 gene were identified from a number of human pathogenic fungi, Candida glabrata, Candida krusei, Candida parapsilosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 19 publications
1
58
0
Order By: Relevance
“…As shown in Fig. 1A, AbA strongly inhibits the growth of filamentous fungi such as A. oryzae, P. oxalicum, and Acremonium sp., previously reported for the yeast Saccharomyces cerevisiae (W303-1A) and other fungi (7)(8)(9)(10)13). However, growth inhibition by AbA was not observed for any Zygomycetes species such as M. hiemalis, R. microsporus, R. pusillus, and A. corymbifera (Fig.…”
Section: Growth Of Fungi Resistant Tosupporting
confidence: 51%
See 1 more Smart Citation
“…As shown in Fig. 1A, AbA strongly inhibits the growth of filamentous fungi such as A. oryzae, P. oxalicum, and Acremonium sp., previously reported for the yeast Saccharomyces cerevisiae (W303-1A) and other fungi (7)(8)(9)(10)13). However, growth inhibition by AbA was not observed for any Zygomycetes species such as M. hiemalis, R. microsporus, R. pusillus, and A. corymbifera (Fig.…”
Section: Growth Of Fungi Resistant Tosupporting
confidence: 51%
“…Aureobasidin A is well known and widely used as an antifungal agent for Eumycetes including yeasts and fungi. It exhibits strong fungicidal activity against many pathogenic fungi, including Candida albicans, Cryptococcus neoformans, and Aspergillus fumigatus (7,8). Recent studies (6) have shown that this antifungal agent inhibits IPC synthase in fungal cells.…”
mentioning
confidence: 99%
“…CPI production requires the product of the AUR1 gene, 45 a protein containing the C2 and C3 active site motifs characteristic for members of the lipid phosphate phosphatase (LPP) superfamily. 57 A database search for novel sequences encoding integral membrane proteins containing the C2 and C3 domains common to Aur1p and LPPs identified three families of candidate SM synthase ( y CSS) genes with homologues in multiple animal species 58 (Fig. 3).…”
Section: Sms Cloning Strategiesmentioning
confidence: 99%
“…57,58 Both groups of enzymes contain a six times membrane-spanning core domain with the termini facing the cytosol and the putative C2 and C3 active site residues facing the exoplasmic leaflet (Fig. 4).…”
Section: Structural Organization and Reaction Chemistry Of Sms Familymentioning
confidence: 99%
“…Pleofungin A more strongly inhibited IPC synthase of A. fumigatus than that of S. cerevisiae in our experimental conditions, however, aureobasidin A showed an opposing tendency in the effects on those enzymes to pleofungin A. Pleofungin A also showed stronger growth inhibition against A. fumigatus and Cryptococcus neoformans than against Candida species and S. cerevisiae. It was previously indicated that the homology between Aspergillus and yeast IPC synthase genes is very low [20,21], regardless of the high homology among the enzymes of Aspergillus species, such as A. fumigatus and A. nidulans. Our data suggested that pleofungin A may recognize the structural differences between the Aspergillus-and yeast-type enzymes, and preferably interact with Aspergillus-type enzymes.…”
Section: Discussionmentioning
confidence: 99%